Deep learning prediction of stress fields in additively manufactured metals with intricate defect networks. (February 2022) - Croom, Brendan P.; Berkson, Michael; Mueller, Robert K.; Presley, Michael; Storck, Steven
Abstract: In context of the universal presence of defects in additively manufactured (AM) metals, efficient computational tools are required to rapidly screen AM microstructures for mechanical integrity. To this end, a deep learning approach is used to predict the elastic stress fields in images of defect-containing metal microstructures. A large dataset consisting of the stress response of 100, 000 random microstructure images is generated using high-resolution Fast Fourier Transform-based finite element (FFT-FE) calculations, which is then used to train a modified U-Net style convolutional neural network (CNN) model. The trained U-Net model more accurately predicted the stress response compared to alternative CNN architectures, exceeded the accuracy of low-resolution FFT-FE calculations, and was generalizable to microstructures with complex defect geometries. The model was applied to images of real AM microstructures with severe lack of fusion defects, and predicted an increase of maximum stress as a function of pore fraction, and higher stress compared to comparable microstructures with circular holes. Together, the proposed CNN offers an efficient and accurate way to predict the structural response of defect-containing AM microstructures. Highlights: U-Net CNN predicts the stress around defects in additively manufactured metals. FFT finite element method generated a large training set of 100, 000 images. Systematic study reveals the importance of CNN architecture on model performance. CNN evaluates ∼40 times faster than FFT finite element method. The trained U-Net quantifies effects of defect morphology on stress response.